Role of the lysophosphatidylinositol/GPR55 axis in cancer. (January 2016) - Falasca, Marco; Ferro, Riccardo
Abstract: Lysophosphatidylinositol (LPI) is a well-known bioactive lipid that is able to activate signalling cascades relevant to cell proliferation, migration, survival and tumourigenesis. It is well-established that the G protein-coupled receptor 55 (GPR55) is the specific receptor for LPI. Several investigations have demonstrated that the signalling pathways activated by LPI through its receptor GPR55 play a pivotal role in different cancer type. This review focuses on the role of the LPI/GPR55 axis, in particular with regards to its pharmacological potential therapeutic exploitation.